A critical review of knowledge on nurses with problematic substance use: The need to move from individual blame to awareness of structural factors. Issue 2 (17th August 2017) - Ross, Charlotte A.; Berry, Nicole S.; Smye, Victoria; Goldner, Elliot M.
Abstract : Problematic substance use (PSU) among nurses has wide‐ranging adverse implications. A critical integrative literature review was conducted with an emphasis on building knowledge regarding the influence of structural factors within nurses' professional environments on nurses with PSU. Five thematic categories emerged: (i) access, (ii) stress, and (iii) attitudes as contributory factors, (iv) treatment policies for nurses with PSU, and (v) the culture of the nursing profession. Conclusions were that an overemphasis on individual culpability and failing predominates in the literature and that crucial knowledge gaps exist regarding the influence of structural factors on driving and shaping nurses' substance use.